Traumatic dental injuries and socioeconomic position – findings from the Children's Dental Health Survey 2013. Issue 6 (12th August 2016) - Blokland, Alex; Watt, Richard G.; Tsakos, Georgios; Heilmann, Anja
Abstract: Objectives: The aim of this study was to assess whether traumatic dental injuries (TDI) were socially graded among children and adolescents in England, Wales and Northern Ireland, using nationally representative data from the Children's Dental Health Survey (CDHS) 2013. Methods: This cross‐sectional study used data from the Children's Dental Health Survey 2013 which was conducted among a nationally representative sample of schoolchildren in England, Wales and Northern Ireland. Children's family socioeconomic position (SEP) was measured through free school meal eligibility and relative area deprivation using the Indices of Multiple Deprivation. The analytical sample included 6707 schoolchildren aged 8, 12 and 15. Multiple logistic regression was used to model the associations between experience of TDI and the two markers of SEP, after adjusting for sex and age. Results: The overall prevalence of traumatic dental injuries to permanent incisors was 9% ( n = 590). There were no statistically significant associations between TDI and either SEP measure. Further subgroup analyses ( n = 2650) showed also no significant associations between TDI and additional SEP markers (parental education and social class). The odds of having sustained a traumatic dental injury were higher for boys than for girls and were greater in older age groups. Conclusions: This study found no significant relationships between the experience of traumatic dental injuries and two markers of family socioeconomic position among children living in England, Wales and Northern Ireland. This implies that rather than specifically targeting the more deprived sectors of society, TDI prevention policies should use upstream public health strategies incorporating a whole‐population approach.